The European Union and customary international law - Bordin, Fernando Lusa 1984-; Müller, Andreas Th. 1977-; Pascual Vives, Francisco José ca. 20./21. Jh (Cambridge University Press, 2022)
The book gathers a group of scholars interested in both public international law and EU law to cover different facets of the relationship between the European Union and customary international law. Considering the distinct perspectives taken by international law and EU law, while also looking into the space in between the two, individual chapters tackle complex questions such as whether and on what bases the European Union is bound by customary international law as a matter of international law and EU law; how the European Union contributes to the development of international custom; and how different stakeholders - the Court of Justice of the European Union, the EU's political organs and EU citizens - rely upon customary rules. The book thus offers a systematic account of the relevance of customary international law for the external relations and internal functioning of what is no doubt the most remarkable regional international organization of our time